Drivers of exploitative and explorative innovation in a collaborative public-sector context. Issue 3 (4th March 2019) - Barrutia, Jose M.; Echebarria, Carmen
ABSTRACT: This paper studies multilevel networks, in which municipalities collaborate with higher tiers of government (upward collaboration), with peers (outward) and with local stakeholders (inward) to discover innovative ways to create public value. A set of hypotheses was developed on the effects of three forms of collaboration (i.e. inward, outward and upward) on two types of innovation (i.e. exploitative and explorative innovation). A range of network and municipality characteristics was also considered. The model was tested by capturing the perceptions of 656 municipal representatives. The research findings provide evidence of complex links between forms of collaboration and types of innovation.